2015
DOI: 10.1016/j.jvir.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Symmetric Hemodialysis Catheters Using Computational Fluid Dynamics

Abstract: The VectorFlow catheter produced less shear-induced platelet activation than the Palindrome catheter and less flow separation than the Palindrome and GlidePath catheters irrespective of line configuration. These findings have potential implications for differences in thrombogenic risk during clinical performance of these catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
50
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 25 publications
(35 reference statements)
6
50
0
2
Order By: Relevance
“…We selected the Tal Palindrome catheter based on its design and literature reports of better survival time and lower complication rates [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…We selected the Tal Palindrome catheter based on its design and literature reports of better survival time and lower complication rates [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…This catheter was developed with the goal of improving catheter performance by optimizing fluid dynamics through helical flow-deflecting interfaces at the catheter tip. This tip design is intended to reduce platelet activation while minimizing recirculation (7,8). Initial clinical experience with this catheter was compared with a conventional split-tip device, the Ash Split Cath catheter (Medcomp, Harleysville, Pennsylvania), in the present retrospective analysis.…”
mentioning
confidence: 99%
“…As stated earlier, simplifying assumptions are often necessary to make a numeric model tractable. However, numerical models of hemodialysis catheters have been performed without making some of the simplifying assumptions used in the study of Clark et al (1). One recent article (4) included a realistic internal jugular vein geometry, nonNewtonian blood rheology, turbulence, and unsteady flow.…”
mentioning
confidence: 99%
“…Unfortunately, similar definitions are not always available. For example, in the analysis of Clark et al (1), the Palindrome catheter demonstrated as much as 345% greater shear-induced platelet activation than the VectorFlow catheter. However, it is not known whether this is a clinically significant difference.…”
mentioning
confidence: 99%
See 1 more Smart Citation